Ag–Cu@FA hydrogel-nanocomposites as catalyst and SERS substrate for the oxidation of TMB. (December 2020) - Cheng, Yong; Wang, Dan; Mei, Yu; Sun, Feifei
Abstract: Ag–Cu@FA hydrogel-nanocomposites were prepared by embedding copper nanoclusters (CuNCs) and silver nanoparticles (AgNPs) in the hydrogel matrix of folic acid (FA). This nanocomposites exhibited high catalytic activity for the oxidation of 3, 3′, 5, 5′-tetramethylbenzidine (TMB) in the presence of H2 O2 . On the basis of the excellent SERS properties of Ag–Cu@FA, the reaction process can be in situ monitored by SERS. Highlights: Ag–CuNCs@FA was prepared by embedded CuNCs and AgNPs within the FA hydrogel matrix. The as-prepared hydrogel-nanocomposites exhibited excellent catalytic performance for the oxidation of TMB. The catalytic oxidation reaction process can be monitored by SERS.